Family Dysfunction, Socio-Economic Status and Effective Learning of Tertiary Level Students in Nigeria - Akintunde, Oluyomi Oyedoyin; Eseyin, Janet (Advances in Social Sciences Research Journal, 2023)
This paper is concerned with family dysfunction and Socio-economic challenges facing students and coping strategies to adopt in paving way for effective learning at the tertiary level. The concepts of family dysfunction and Socio-economic status and challenges posed are discussed. Impacts of these factors on students’ learning include loss of concentration, poor academic achievement, low self-esteem, indiscipline acts, mental health issues and dropping out of school. Coping strategies proposed for family dysfunction and Socio-economic status challenges include positive mindset, therapy, acquisition of creative skills, cutting costs, and acquisition of entrepreneurial and technology skills. Recommendations made include Self-determination for success, Productive ventures, Provision of adequate school vehicles for transportation and internet connectivity for schools.